Anorectal toxicity of external beam radiotherapy in the treatment of prostate cancer. (May 2014) - Bajwa, Adeel; Raeburn, Amanda; Taylor, Stuart; Cohen, Richard; Payne, Heather; Emmanuel, Anton
Introduction: Maximising radiotherapy dosage is associated with better tumour response in prostate cancer. High dose three-dimensional conformal radiotherapy (3D CRT) has allowed dose escalation to be safely achieved and the current standard dose in the UK with this technique is 74 Grays (Gy). Documenting normal tissue tolerance is critical and forms the basis of this prospective study of anorectal toxicity. Patients and methods: Seventeen consecutive men (median age 72 (range 50–79) years) with localised or locally advanced prostate cancer treated with 74 Gy of 3D CRT were studied. Wexner incontinence scores, comprehensive anorectal physiology and endoanal ultrasound were measured before and four months after completing treatment. Results: Wexner incontinence scores increased from a median of 0 to 1 (range 0–6) with treatment ( p =0.001). Patients developed faecal urgency (7/17), passive faecal loss (5/17) or a combination of both (3/17) as new anorectal symptoms. No patients reported episodes of frank faecal incontinence. A significant decline in rectal mucosal electrosensitivity (mean (standard deviation (SD)) thresholds increasing from 24.7 (10.7) to 34.3 (9.3) mA after treatment, p =0.003) and an increase in rectal elastance (mean (SD) of 0.056 (0.03) mm Hg/ml to 0.078 (0.036) mm Hg/ml pre- and post-treatment respectively, p =0.0181) was seen. No changes in anal canal manometry, rectal distension volumes and endoanal ultrasound were noted. Conclusions: Early anorectal symptoms are common after 3D CRT for prostate cancer. Rectal injury is evident with an increase in wall stiffness and a decrease in mucosal sensitivity. Longer term studies monitoring anorectal toxicity are warranted.